Evolutionary origin and functional specialization of Dormancy‑Associated MADS box (DAM) proteins in perennial crops - Quesada-Traver, Carles; Lloret, Alba; Carretero-Paulet, Lorenzo; Badenes, María L.; Ríos, Gabino (Springer Nature, 2022)
Background: Bud dormancy is a phenological adaptation of temperate perennials that ensures survival under winter temperature conditions by ceasing growth and increasing cold hardiness. SHORT VEGETATIVE PHASE (SVP)-like factors, and particularly a subset of them named DORMANCY-ASSOCIATED MADS-BOX (DAM), are master regulators of bud dormancy in perennials, prominently Rosaceae crops widely adapted to varying environmental conditions. Results: SVP-like proteins from recently sequenced Rosaceae genomes were identifed and characterized using sequence, phylogenetic and synteny analysis tools. SVP-like proteins clustered in three clades (SVP1–3), with known DAM proteins located within SVP2 clade, which also included Arabidopsis AGAMOUS-LIKE 24 (AthAGL24). A more detailed study on these protein sequences led to the identifcation of a 15-amino acid long motif specifc to DAM proteins, which afected protein heteromerization properties by yeast two-hybrid system in peach PpeDAM6, and the unexpected fnding of predicted DAM-like genes in loquat, an evergreen species lacking winter dormancy. DAM gene expression in loquat trees was studied by quantitative PCR, associating with inforescence development and growth in varieties with contrasting fowering behaviour. Conclusions: Phylogenetic, synteny analyses and heterologous overexpression in the model plant Arabidopsis thaliana supported three major conclusions: 1) DAM proteins might have emerged from the SVP2 clade in the Amyg‑daloideae subfamily of Rosaceae; 2) a short DAM-specifc motif afects protein heteromerization, with a likely efect on DAM transcriptional targets and other functional features, providing a sequence signature for the DAM group of dormancy factors; 3) in agreement with other recent studies, DAM associates with inforescence development and growth, independently of the dormancy habit.